Innovative healthcare marketing promotion, social marketing and outpatients’ satisfaction in selected private hospitals in Lagos Metropolis - Ismail Tubosun Arebi; Samson Adewumi (International Journal of Academe and Industry Research)
There is hardly any study that has investigated healthcare promotion and social marketing in understanding hospital outpatient satisfaction in Lagos Metropolis. This study interrogate how innovative healthcare promotion and social marketing can be used to understand hospital outpatient satisfaction in Lagos metropolis. The research design supports the assumption of the cross-sectional-survey where data were collected from many samples at a single and short point in time. A total of 371 participants were recruited through stratified sampling from 18 modern care hospitals in 10 Local Government Areas considered as metropolitan areas. A researcher-designed Likert-scale questionnaire with reliable coefficient. SPSS (29 Version) software was used to analyse the data including the mean, standard deviation and multiple regression analysis. Innovative healthcare promotion including personal selling (β = 0.573, t=5.658, p<0.05) and direct marketing (β = 0.436, t=4.459, p<0.05) significantly predicted outpatient satisfaction, while advertising (β = -0.059, t=-1.171, p>0.05 at 0.242) was insignificant and weak with negative influence (β = -0.059). Social marketing including community engagement (β = 0.396, t=5.595, p<0.05) and healthcare matchmaking (β = 0.512, t=10.235, p<0.05) significantly predicted outpatient satisfaction, while social media management (β = 0.070, t=1.233, p>0.05 at 0.218) was insignificant (β = 0.070). The study concluded that social marketing in healthcare is critical for improving outpatient satisfaction. Healthcare organisations must look beyond traditional marketing strategies while employing innovative healthcare marketing strategies to reach different target audiences. Although there is an emphasis on the health benefits that trigger a quality-based product strategy to sell itself, the healthcare organisation is recommended to strengthen the quality of its innovative healthcare goods and services for outpatient improved satisfaction.